2015
DOI: 10.1186/s40001-015-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

The value of liver resection for focal nodular hyperplasia: resection yes or no?

Abstract: BackgroundFocal nodular hyperplasia (FNH) are benign lesions in the liver. Although liver resection is generally not indicated in these patients, rare indications for surgical approaches indeed exist. We here report on our single-center experience with patients undergoing liver resection for FNH, focussing on preoperative diagnostic algorithms and quality of life (QoL) after surgery.MethodsMedical records of 100 consecutive patients undergoing liver resection for FNH between 1992 and 2012 were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
10
0
2
Order By: Relevance
“…However, there were more males than females in this study, which was inconsistent with the literature reports [17], which may be related to the small sample size. HCC is more common in middle-aged and elderly men with acute onset, abdominal pain, and background of hepatitis or cirrhosis, which is similar to that reported in the literature [18][19][20].…”
Section: Discussionsupporting
confidence: 86%
“…However, there were more males than females in this study, which was inconsistent with the literature reports [17], which may be related to the small sample size. HCC is more common in middle-aged and elderly men with acute onset, abdominal pain, and background of hepatitis or cirrhosis, which is similar to that reported in the literature [18][19][20].…”
Section: Discussionsupporting
confidence: 86%
“…The actual prevalence of these diseases in the general population is not low, but only a small proportion of the patients have undergone HR because a majority of these diseases are not indicated for any surgical treatment. 14 15 16 …”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that hepatic resection was a valuable therapeutic option in the treatment of either symptomatic FNH or when malignancy could not be ruled out. If clinically indicated, liver resection for FNH represents a safe approach and may lead to significant improvement in of quality of life, especially in symptomatic patients 9…”
Section: Discussionmentioning
confidence: 99%